Supportive Group Therapy untuk Menurunkan Kecemasan Ibu Hamil di Wilayah Puskesmas Srandakan - Fahrunnisa Lanjarto; Raras Indah Fitriana (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
Pregnancy is time when a person experiences many changes, both physically and psychologically, making them more vulnerable to stress. This case happens because pregnant women experience hormonal changes that affect psychological and physical conditions during the pregnancy process. This study aims to determine the effect of group therapy using supportive techniques coupled with the provision of information needed to reduce anxiety in pregnant women. The data collection methods used in this study were observation, interviews, Focused Group Discussion (FGD), as well as pre-test and post-test using the Beck Anxiety Inventory (BAI). The research design using quasi-experimental with pre-test and post-test without control, the sample in the study consisted of 7 pregnant women who had mild to severe anxiety levels. The results of data analysis using non-parametric test with the Wilcoxon test showed a value of z = 2.731 and a value of p = 0.018 (p <0.05). The results showed a significant decrease in anxiety scores before and after following the group therapy process. Based on the results of the study, it can be concluded that there is an effect of supportive group therapy on pregnant women at the Srandakan Public Health Center.